2018
DOI: 10.21873/anticanres.12803
|View full text |Cite
|
Sign up to set email alerts
|

CT Texture Analysis of Ductal Adenocarcinoma Downstaged After Chemotherapy

Abstract: This evaluation may represent an added value in tumor tissue changes judgment and can be extremely useful to diagnose downstaging in those cases with no evident downsizing after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…The results showed that kurtosis differed significantly before and after neoadjuvant therapy in the downstaged group. No significant changes between texture features were found in the disease progression group [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that kurtosis differed significantly before and after neoadjuvant therapy in the downstaged group. No significant changes between texture features were found in the disease progression group [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies with missing data on best predictive performance (accuracy or area under the curve) were excluded from these plots. No feature reduction or adjustment for multiple testing was performed in 14/60 (23%) of studies, which may have resulted in overfitting of models [ 22 24 , 37 , 39 – 44 , 67 , 73 75 ]. Study populations were relatively small compared to the number of parameters analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be used to formulate the optimal treatment plan for PDAC patients. Ciaravino et al [ 61 ] investigated the added value of CT texture analysis in estimating tissue changes in PDAC downsized and resected after chemotherapy. The results suggested that the change of kurtosis before and after treatment showed a statistically significant difference, suggesting that CT texture analysis can assess tumor heterogeneity, tissue changes, and tumor downstaging in PDAC cases with no significant alteration in tumor size after NAT.…”
Section: Response Assessment Of Pdac After Natmentioning
confidence: 99%
“…Some of these parameters fall within the general concept of Radiomics, i.e., the analysis of medical images aimed at obtaining quantitative information that cannot be detected through their simple visual observation [8,9]. Radiomics has been applied with excellent results to various radiological fields, mainly in oncology, often reaching a significant prognostic value [10][11][12][13]. It has been used in the distinction between inflammatory/infectious and oncological disease [14], in the discrimination between primary tuberculous pneumonia and acquired pneumonia in children [15] and in the prediction of the onset of immunotherapy-induced pneumonia [16].…”
Section: Introductionmentioning
confidence: 99%